Comparison of the Efficacy of Glucagon-Like Peptide-1 Receptor Agonists in Patients With Metabolic Associated Fatty Liver Disease: Updated Systematic Review and Meta-Analysis - Dai, Yuzhao; He, He; Li, Sheyu; Yang, Lidan; Wang, Xia; Liu, Zhi; An, Zhenmei (Frontiers in Endocrinology, 2021)
Aims: Metabolic associated fatty liver disease (MAFLD) is the most common cause of chronic liver disease and is a major health and economic burden in society. New drugs are urgently needed to treat MAFLD. This systematic review and meta-analysis was conducted to evaluate the efficacy of glucagon-like peptide-1 receptor agonists (GLP-1RAs) in patients with MAFLD. Method: We searched PubMed, Embase, Cochrane Library database, and Web of Science since 1977. We selected all randomized controlled trials which met the inclusion and exclusion criteria and evaluated the quality of evidence. A random-effects meta-analysis was performed to assess all the primary and second outcomes. Results: Eight randomized controlled trials, including 396 patients, of which 265 patients had type 2 diabetes mellitus, met the inclusion criteria. Compared with the placebo or active agents group, the GLP-RA group showed a significant reduction in the liver fat content [weight mean difference (WMD) -3.17%, 95%CI -5.30 to -1.03, P < 0.0001] , body weight (WMD -4.58 kg, 95%CI -8.07 to -1.10, P = 0.010), waist circumference (WMD -3.74 cm, 95%CI -6.73 to -0.74, P = 0.010), alanine aminotransferase (WMD -10.73 U/L, 95%CI -20.94 to -0.52, P = 0.04), γ- glutamyl transferase (WMD -12.25 U/L,95% -18.85 to -5.66, P = 0.0003, with I²=23%), fasting blood glucose (MD, -0.36 mmol/L; 95%CI, -0.69 to -0.03, P = 0.030) and hemoglobin A1c (WMD -0.36%, 95%CI -0.52 to -0.19, P < 0.0001). The reported adverse events were gastrointestinal complications with no serious adverse events, and most symptoms were relieved within 1-2 weeks after dose titration. Conclusion: GLP-RAs may improve liver injury and metabolic disorder in patients with MAFLD, regardless of the presence of type 2 diabetes mellitus. The benefits of GLP-RAs treatment outweigh the adverse effects of drugs in patients with MAFLD.